2014
DOI: 10.2478/nuka-2014-0021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of circulating endothelial cells in the rat after acute and fractionated whole-body gamma irradiation

Abstract: Abstract.Purpose: Damage to vascular endothelial cells is a well recognised complication of the irradiation. Our objective was to determine the gamma-irradiation effect on the rat circulating endothelial cells (CEC). Material and methods: Eight-week old rats were divided into four groups: group 1 -rats were exposed to acute whole--body gamma irradiation with a wide range of single doses (0.5, 1, 2, 4 and 8 Gy), group 2 -rats were exposed to fractionated low doses of irradiation (0.1, 0.5 and 1 Gy) every three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…These cells are heterogeneous in size (15–50 µm), carry the markers of ECs (e.g., VWF, CD144 and CD146), but not leukocyte markers (CD45), and serve as noninvasive markers of EC damage and dysfunction. Al-Massarani and colleagues demonstrated a reduction in circulating ECs after acute- and fractionated-dose gamma irradiation in rat peripheral blood, with an incomplete recovery 2 months postirradiaton (91), and in patients undergoing chemotherapy (92, 93). The presence of systemic signalers of processes, such as the oxidative stress pathway and inflammation, is attractive since there is vast potential for a noninvasive or minimally invasive source of biomarkers for early and delayed progression of injury.…”
Section: Introductionmentioning
confidence: 99%
“…These cells are heterogeneous in size (15–50 µm), carry the markers of ECs (e.g., VWF, CD144 and CD146), but not leukocyte markers (CD45), and serve as noninvasive markers of EC damage and dysfunction. Al-Massarani and colleagues demonstrated a reduction in circulating ECs after acute- and fractionated-dose gamma irradiation in rat peripheral blood, with an incomplete recovery 2 months postirradiaton (91), and in patients undergoing chemotherapy (92, 93). The presence of systemic signalers of processes, such as the oxidative stress pathway and inflammation, is attractive since there is vast potential for a noninvasive or minimally invasive source of biomarkers for early and delayed progression of injury.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, our group reported a gradual decline in CEC count post irradiation (AL-Massarani and Almohamad, 2014).…”
Section: A B D Cmentioning
confidence: 63%
“…In a previous study, our group reported a gradual decline in CEC count post irradiation ( AL-Massarani and Almohamad, 2014 ). Originally, the results of this study ( Figure 6 ) suggest that injection of RSV attenuates radiation-induced CEC apoptosis in rats.…”
Section: Discussionmentioning
confidence: 77%